Power Point Learning Media on Students' Interest in Learning in Social Sciences Subjects at SD Inpres Paranga District. Ulu Ere District. Bantaeng - Nurlaelah Nurlaelah; Nurdin Nurdin; Rubianto Rubianto (International Journal of Multilingual Education and Applied Linguistics, 2024)
The main problem in this research is whether there is an effect of using interactive PowerPoint learning media on fourth grade students' interest in learning in social studies subjects at SD Inpres Parang, Ulu Ere District, Bantaeng Regency. Meanwhile, the aim of the research carried out was to determine the effect of using interactive power point learning media on fourth grade students' interest in learning in social studies subjects at SD Inpres Paranga District. Ulu Ere District. Bantaeng. This type of research is pre-experimental research with a quantitative approach. The sample in this research was fourth grade students at SD Inpres Paranga, Ulu Ere District, Bantaeng Regency. The results of the research show that there is an influence of the use of interactive power point media on the learning interest of fourth grade students at SD Paranga Presidential Instruction, District. Ulu Ere Bantaeng Regency. The design used in this experimental research is one group pretest-posttest design. This can be seen from the comparison between the pre-test and post-test scores. The average pre-test score obtained was 55.47. The average score was in the 55-64 interval which was included in the medium category. However. The average posttest value obtained was 81.94 which was in the 65-84 interval, which means it was in the high category. The research results were obtained by researchers using at distribution table with a significance level of a = 0.05 and d. b = N-1 =17-1=16 then we get t0.05 = 1.024. After obtaining t Count = 10.45 and t Table = 1.024, we get t Count > t Table or 10.45 > 1.024 so it can be concluded that the use of Interactive Power Point Media has an effect on the learning interest of class IV students at SD Inpres Paranga District. Ulu Ure District. Bantaeng. So it can be concluded that H0 is rejected and Ha is accepted. This means that there is a significant difference in the influence of the use of interactive power point media on interest in learning social studies among fourth grade students at SD Inpres Paranga District. Ulu Ere District. Bantaeng.